Fluoride-mediated dephosphonylation of alpha-diazo-beta-carbonyl phosphonates - Phatake, Ravindra S.; Mullapudi, Venkannababu; Wakchaure, Vivek C.; Ramana, Chepuri V. (Organic Letters, 2017)
The possibility of fluoride-mediated selective dephosphonylation of alpha-diazo-beta-carbonyl phosphonates such as the Ohira-Bestmann reagent has been proposed and executed. The resulting alpha-diazocarbonyl intermediates undergo a (3 + 2)pcycloaddition at room temperature with conjugated olefins and benzynes. Interestingly, under the current conditions, the resulting cycloaddition products underwent either N-acylation (with excess alpha-diazo-beta-carbonyl phosphonates) or Michael addition (with conjugated olefins).

Phenol oxidative dearomatization of modified nucleoside templates: a simple access to the c7-spiroannulated octosyl acid framework - Mullapudi, Venkannababu; Bhogade, Ravindra B.; Deshpande, Mukund V.; Ramana, Chepuri V. (Synthesis-Stuttgart, 2017)
Phenol oxidative dearomatization and cyclization has been executed successfully on nucleoside templates to synthesize C7-spiroannulated perhydrofuropyran nucleosides and C6-spiroannulated perhydrofurofuran nucleosides as novel analogues of octosyl acid and related peptidyl nucleosides.
Keywords: Analogs; antibiotics; Biosynthesis; Chitin synthase; Derivatives; Ezomycins; Glucose Diacetonide Natural-products; Griseofulvin; Malayamycin; Modified nucleosides; Moiety; Peptidyl Glycosides; Phenol Oxidative Dearomatization; Vorbruggen Glycosylation

Attempted synthesis of central furopyran core of diocollettines A via a gold-catalyzed cascade 1,6-diyne cycloisomerization process - Mullapudi, Venkannababu; Ramana, V, Chepuri (Tetrahedron Letters, 2020)
Herein, we describe an Au-catalyzed cascade diyne cycloisomerization process that was projected to construct the central furopyran bicyclic core of Diocollettines A. Our intended strategy for the annulation of the third thf ring is based on epoxidation and subsequent intramolecular acetalization. However, the initial alkynol cyclization occurred in an undesired 5-exo-dig mode, ultimately leading to an undesired furopyran. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: 1; 6-Hexadiyne; Alkynol cycloisomerization; Diocollettines A; Gold-catalysis; Total synthesis

Total synthesis of (+)-petromyroxol, (-)-iso-petromyroxol, and possible diastereomers - Mullapudi, Venkannababu; Ahmad, Iram; Senapati, Sibadatta; Ramana, V, Chepuri (ACS Omega, 2020)
The total synthesis of (+)-petromyroxol (1) and its seven diastereomers including the ()-tso-petromyroxol (2) is described. The employed strategy involves the use of easily available CS-epimeric epoxides 5 and 5' and nonselective anomeric C1-allylation, proceeding with or without inversion at C2 thereby giving the possibility of synthesizing all possible diastereomers. Extensive two-dimensional (2D) NMR analyses of all eight diastereomers have been carried out to assign the chemical shifts of the central carbons land the corresponding attached hydrogens and to learn how the C/H-chemical shifts of the tetrahydrofuran ring were influenced by the adjacent centers.

Total synthesis of (+)-petromyroxol (vol 56, pg 3933, 2015) - Mullapudi, Venkannababu; Ramana, Chepuri V. (Tetrahedron Letters, 2020)

Iridium-catalyzed synthesis of pyrazolone fused 1,4-dihydrocinnolin-3-one employing alpha-diazotized Meldrum's acid - Kulkarni, Anand M.; Mullapudi, Venkannababu; Ramana, Chepuri Venkata (ARKIVOC, 2022)
The [Iri-catalysed carbenoid insertion and cyclization of N-arylpyrazolones has been carried out with alpha-diazotized Meldrum's acid to access tricyclic pyrazolone fused 1,4-dihydrocinnolin-3-one derivatives. Further, the selective reduction of these tricyclic derivatives has been studied under Birch reduction conditions.
Keywords: ?-diazotized Meldrum's acid; C-H activation; carbene Insertion; cinnoline derivatives; N-arylpyrazolones; [Iri-Catalysis